Segmenting, Targeting, and Positioning Strategies in the formation of Mahar Agung Organizer's Brand Image - Sukirno, Adelia Firansiska; Kustini, Kustini (PT FORMOSA CENDEKIA GLOBAL, 2024)
In order to create a competitive advantage, the strategy that is considered effective in overcoming it is the existence of the right strategy, for example the STP (Segmenting, Targeting, Positioning) strategy. This research focuses on analyzing the marketing strategy of Mahar Agung Organizer Event Organizer (EO) on brand image formation. This research is useful in knowing how wedding organizer services maximize their marketing strategies to get as much profit as possible. This research is a type of qualitative research that uses descriptive analysis. The results of this study indicate a segmentation strategy based on geographic, demographic, behavioral, and psychographic segmentation. The focus of Mahar Agung Organizer's target is from the upper middle class community with an age range of 20-60 years in the East Java Province area. The implementation of the right positioning and targeting has succeeded in forming a positive brand image of Mahar Agung Organizer as a top quality EO in handling traditional Javanese weddings.